2022
DOI: 10.47162/rjme.63.2.11
|View full text |Cite
|
Sign up to set email alerts
|

The mast cell reaction in premalignant and malignant lesions of the head and neck

Abstract: Head and neck squamous cell carcinoma (HNSCC) is one of the most frequent and aggressive neoplasms of this anatomical region. Many studies evaluated the neoplastic cells, but few works focused on the tumor microenvironment. In the present study, we investigated the distribution and mast cell density (MCD) in malignant and premalignant lesions of the oral cavity, tongue, pharynx, and larynx. There were analyzed 52 specimens of HNSCC, and 15 biopsies taken from patients with dysplasia. Results were compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Mast cells, a type of white blood cells, have been identified as significant players in the development and progression of oral tumors, specifically oral squamous cell carcinoma (OSCC) and head and neck squamous cell carcinoma (HNSCC). Research studies have found that the density of mast cells (MCD) increases significantly from normal oral mucosa to malignant lesions, indicating a potential correlation with tumor progression and prognosis [21]. The influence of mast cells on tumor cell proliferation and invasion rates has been established in OSCC, with CC chemokine ligand 2 (CCL2) identified as a possible mediator of this interaction.…”
Section: C) Oral Cancermentioning
confidence: 99%
“…Mast cells, a type of white blood cells, have been identified as significant players in the development and progression of oral tumors, specifically oral squamous cell carcinoma (OSCC) and head and neck squamous cell carcinoma (HNSCC). Research studies have found that the density of mast cells (MCD) increases significantly from normal oral mucosa to malignant lesions, indicating a potential correlation with tumor progression and prognosis [21]. The influence of mast cells on tumor cell proliferation and invasion rates has been established in OSCC, with CC chemokine ligand 2 (CCL2) identified as a possible mediator of this interaction.…”
Section: C) Oral Cancermentioning
confidence: 99%